2007
DOI: 10.1242/dev.003616
|View full text |Cite
|
Sign up to set email alerts
|

Zfrp8, theDrosophilaortholog ofPDCD2,functions in lymph gland development and controls cell proliferation

Abstract: We have identified a new gene, Zfrp8, as being essential for hematopoiesis in Drosophila. Zfrp8 (Zinc finger protein RP-8) is the Drosophila ortholog of the PDCD2 (programmed cell death 2) protein of unknown function, and is highly conserved in all eukaryotes. Zfrp8 mutants present a developmental delay, lethality during larval and pupal stages and hyperplasia of the hematopoietic organ, the lymph gland. This overgrowth results from an increase in proliferation of undifferentiated hemocytes throughout developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 55 publications
3
50
0
Order By: Relevance
“…2 C and D; n = 10). Cyclin A accumulates during the transition from late S/G2 phase to mitosis (16). Abundant cyclin A was seen in ARF1-depleted lobes, indicating the cells were ready to enter mitosis ( Fig.…”
Section: Arf1 Depletion In the Lymph Gland Affects Cell Proliferationmentioning
confidence: 89%
“…2 C and D; n = 10). Cyclin A accumulates during the transition from late S/G2 phase to mitosis (16). Abundant cyclin A was seen in ARF1-depleted lobes, indicating the cells were ready to enter mitosis ( Fig.…”
Section: Arf1 Depletion In the Lymph Gland Affects Cell Proliferationmentioning
confidence: 89%
“…Zfrp8 was originally identified by its strong hematopoietic phenotype and lethality (Minakhina et al, 2007). Clonal analysis in lymph glands showed that Zfrp8 is essential in stem cells, as no persistent clones were recovered, but is dispensable in more mature cells, as transient Zfrp8 clones had the same developmental potential as wild-type clones (Minakhina and Steward, 2010), for clone nomenclature see Fox et al (Fox et al, 2008).…”
Section: Zfrp8 Is Essential In Follicle Stem Cellsmentioning
confidence: 99%
“…Transgenic fly lines were created following standard protocols (Rubin and Spradling, 1982; Brand and Perrimon, 1993). For RNAi experiments, flies were raised at 29°C.For genetic interaction experiments, the Zfpr8 null allele (Minakhina et al, 2007) was recombined/combined with alleles of each gene tested (supplementary material Table S1A,B). Eggs were collected from 5-to 7-day-old females and allowed to develop for 2 days at 25°C for examination of egg phenotypes.…”
mentioning
confidence: 99%
“…Embryos and larval lymph glands were dissected, fixed, immunostained and analyzed as described (Jung et al, 2005;Minakhina et al, 2007). Antibodies specific for lamellocytes (L1) and for plasmatocytes (P1) were obtained from Dr I. Ando (Biological Research Center, Szeged, Hungary) and used at 1:400 dilution; rabbit anti-PPO2 antibody from George Christophides (Imperial College, London, 1:2000), rabbit anti-Pxn antibody from John Fessler and Sergey Sinenko (UCLA, 1:700), and anti-Antp antibody from the Developmental Studies Hybridoma Bank (Glicksman and Brower, DSHB, 1:20) were used as CC, PH and PSC markers, respectively.…”
Section: Immunochemistry and Imagingmentioning
confidence: 99%
“…Loss of Zfrp8 causes a unique phenotype in Drosophila. The lymph gland is enlarged already in midembryogenesis and by the late third instar larval stage, the lymph gland size is increased 10 to 50 times, accompanied by lamellocyte overproliferation (Minakhina et al, 2007).…”
Section: Research Reportmentioning
confidence: 99%